2020
DOI: 10.1002/celc.202000186
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Quantum Dots Induce Uniform Lithium Plating in a Sandwiched Metal Anode

Abstract: Lithium (Li) metal anodes are demanded by high-energy Li batteries because Li has the highest capacity and low electrode potential. However, Li metal anodes usually show poor cyclability and unsafe deposition at anode/separator interfaces, which may increase the risk of short circuits. In this work, we fabricate a sandwiched structure of reduced graphene oxides (rGO) with silicon (Si) quantum dots (QDs) as the inducing agents between rGO layers. Because of the lithiophilicity of Si QDs, Li growth is favorably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…260 Towards stabilizing the Li metal anode, QDs and QD based composites have been used as a matrix for dendrite-free lithium deposition, as a component in the solid-state electrolyte to improve the ionic conductivity, for increasing the Li + transference number and reducing interfacial resistance with lithium metal and as an electrolyte additive to regulate homogeneous lithium deposition at the anode. 55,261 One of the strategies to stabilize lithium metal is to guide the metal deposition away from the anode/electrolyte interface during charging. Metals such as gold (Au), zinc (Zn), silicon (Si), copper (Cu), cobalt (Co), etc.…”
Section: Quantum Dot Based Nanocomposite Electrodes For Lithium Metal Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…260 Towards stabilizing the Li metal anode, QDs and QD based composites have been used as a matrix for dendrite-free lithium deposition, as a component in the solid-state electrolyte to improve the ionic conductivity, for increasing the Li + transference number and reducing interfacial resistance with lithium metal and as an electrolyte additive to regulate homogeneous lithium deposition at the anode. 55,261 One of the strategies to stabilize lithium metal is to guide the metal deposition away from the anode/electrolyte interface during charging. Metals such as gold (Au), zinc (Zn), silicon (Si), copper (Cu), cobalt (Co), etc.…”
Section: Quantum Dot Based Nanocomposite Electrodes For Lithium Metal Batteriesmentioning
confidence: 99%
“…Thus alloy nuclei with high lithiophilicity offer a low lithium-ion diffusion barrier and a dendrite-free anode can be realized. 264 Zhang et al 55 demonstrated such an engineered matrix constructed with Si QDs sandwiched between rGO sheets. Si is more lithiophilic than rGO and favors the Li nucleation and plating between rGO layers.…”
Section: Quantum Dot Based Nanocomposite Electrodes For Lithium Metal Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Matching the NMC532 (LiNi 0.5 Mn 0.3 Co 0.2 O 2 ) electrode, full battery cycle for 380 cycles has almost no capacity fading. Zhao et al 118 fabricated a sandwich structure between rGO layers using silicon quantum dots (SiQDs) as the lithiophilic inducing agents. The ultrafine size of SiQDs enables the parallel stacking of rGO layers without uneven grain inclusions.…”
Section: Alloying-based Lithiophilic Sitesmentioning
confidence: 99%
“…[ 1‐4 ] However, the dissolution of intermediate polysulfides in the electrolyte leads to the rapid capacity fading and the corrosion of Li metal anode. [ 5‐7 ] What's worse, sluggish reaction kinetics of polysulfide conversion lower efficient utilization of sulfur species and lead to polysulfide accumulation, which would aggravate the shuttling effect. [ 8‐9 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%